THE OLYMPIC GAMES AS ACTUATOR OF AN INTERNATIONAL COOPERATION AND STRENGTHENING OF INTERSTATE FRIENDLY RELATIONS - Dušan Simonović; Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Ever since it has been founded, the Montenegrin Olympic Committee has registered international cooperation followed thorough principles of olympism development as well as its important role in the international cooperation and strengthening of interstate friendly relations. The Olympic Games have always been consisted of a lot of programs having the common aim-making the world a better place through sports. Most of them are continual, and without press. A lot of programs involve close international cooperation with different sports organisations, governmental and non-governmental sector, sportsmen, businessmen, etc. In spite of the popularity enjoyed by the Olympic Games, they were never imagined to be the purpose for themselves. Also, they represent means for achieving other, socially very important aims promoting sports activity, especially among the youths, with an accent on friendship, fair play, respecting other nations and other values.